2013
DOI: 10.5897/ajps12.081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crop rotation and residue management on bread wheat

Abstract: The objective of this study was to determine the influence of crop rotation and crop residue management on wheat yield and yield components with four crop rotations [wheat-wheat-wheatrapeseed-wheat (WWWRW), wheat-sugar beet-wheat-potato-wheat (WSWPW), wheat-maize-wheatpotato-wheat (WMWPW) and wheat monoculture for the whole period (WWWWW)] and three levels of retaining crop residues to soil (0, 50 and 100% produced crop residues to soil) were allocated to main and sub plots, respectively. Results showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
3
3
0
2
Order By: Relevance
“…Also, there were significant increases on wheat plant height at final harvest as a result of crop residues incorporated in soil surface layer in crop sequence 1, 2, 3 and 4 as compared with its counterpart sequences but with crop residues completely removed. These results are similar to those mentioned by Feizabady, 2013;Rahman, 2004 on wheat plants.…”
Section: Plant Height (Cm)supporting
confidence: 82%
See 2 more Smart Citations
“…Also, there were significant increases on wheat plant height at final harvest as a result of crop residues incorporated in soil surface layer in crop sequence 1, 2, 3 and 4 as compared with its counterpart sequences but with crop residues completely removed. These results are similar to those mentioned by Feizabady, 2013;Rahman, 2004 on wheat plants.…”
Section: Plant Height (Cm)supporting
confidence: 82%
“…The 1000 grains weight varied from 45.0 g in sequence 1 without crop residues to 49.7 g in sequence 4 +CR ( Table 7). The results of this field experiment are in accordance with those obtained by other investigators confirming the stimulative effect of crop residues and crop rotation, especially on newly cultivated soils with low organic matter for improvement of wheat growth and yield components (Feizabady 2013;Jan et al, 2012;Usman et al 2014).…”
Section: Seed Index (G)supporting
confidence: 81%
See 1 more Smart Citation
“…Most of the crops, including wheat, are grown as monocultures. This method of growing involves increased stress on plants from both biotic and abiotic factors [1][2][3]. Studying plant metabolism characteristics is a natural step towards the improvement of growth and productivity of plants, especially through the intensification of secondary metabolic processes, such as synthesis of phenolic compounds and lignin-an important element of cell walls.…”
Section: Introductionmentioning
confidence: 99%
“…As residues are good sources of plant nutrients, both farmers and researchers have shown more curiosity in management of residue types. Usually, it acts as valuable management tool because of high costs of inorganic fertilizers and less yield in monoculture cropping systems [18]. Research studies have revealed that residues enhanced soil fertility, crop productivity, reduced wind and water erosion and prevented nutrients leaching and losses by run-off [19].…”
Section: Introductionmentioning
confidence: 99%